1993
DOI: 10.1038/hdy.1993.154
|View full text |Cite
|
Sign up to set email alerts
|

Synaptonemal complexes in female and male meiotic prophase of Ephestia kuehniella (Lepidoptera)

Abstract: Synaptonemal complex (SC) complements of oocyte and spermatocyte pachytene nuclei in the Mediterranean flour moth, Ephestia kuehniella, were investigated using a microspreading technique and electron microscopy. In both sexes, three autosomal SCs could be identified by their morphological landmarks; one SC has a prominent knob and two SCs have nucleolus organizer regions. In a later stage of SC development in oocytes, the two nucleolar SCs displayed electron dense terminal modifications of the lateral elements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 26 publications
3
25
0
Order By: Relevance
“…Similar results were sporadically recorded for species of other taxa that possess both holocentric chromosomes and achiasmatic meiosis, e.g. Lepidoptera, Mantodea and Trichoptera [Gassner, 1969;Rasmussen, 1977;Rasmussen and Holm, 1979;John, 1990;Marec and Traut, 1993;Wolf et al, 1997]. In Scorpiones, the maintenance of SCs in late meiosis I likely provides the connection required for the correct and balanced segregation of bivalent-like elements and chromosome chains during meiosis I, such as suggested by Rasmussen [1977] for Bombyx mori (Lepidoptera).…”
Section: Discussionsupporting
confidence: 63%
“…Similar results were sporadically recorded for species of other taxa that possess both holocentric chromosomes and achiasmatic meiosis, e.g. Lepidoptera, Mantodea and Trichoptera [Gassner, 1969;Rasmussen, 1977;Rasmussen and Holm, 1979;John, 1990;Marec and Traut, 1993;Wolf et al, 1997]. In Scorpiones, the maintenance of SCs in late meiosis I likely provides the connection required for the correct and balanced segregation of bivalent-like elements and chromosome chains during meiosis I, such as suggested by Rasmussen [1977] for Bombyx mori (Lepidoptera).…”
Section: Discussionsupporting
confidence: 63%
“…Similar to another pyralid moth, Ephestia kuehniella (n = 30), two autosomal NOR-bivalents were observed in pachytene complements (cf. Marec and Traut 1993). On the contrary, a single NOR-bivalent was reported in several other lepidopterans.…”
Section: Discussionmentioning
confidence: 90%
“…They concluded that crossing-over contributes to the sterility in F 1 males mostly through the formation of multiple translocations. Since female meiosis is achiasmate during oogenesis, this factor cannot play a role in the sterility level of F 1 females (Rasmussen 1977, Traut 1977, Nokkala 1987, Marec and Traut 1993b). …”
Section: Sex-specific Differences In Inherited Sterilitymentioning
confidence: 98%